Pelestarian Tari Sayak Di Sanggar Seni Buluh Batuah Sayak Baguno Di Desa Air Batu - Ayu Ulandari; Darmawati Darmawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The aim of this research is to reveal and describe the preservation of Sayak Dance in Buluh Betuah Sayak Baguno Art Studio in Air Batu Village This type of research is qualitative research with descriptive method The instrument of this research is the researcher himself and assisted by supporting instruments such as writing tools, camera and flash drive Data in this research uses primary and secondary data Data collection techniques are carried out through observation, interviews and documentation The steps of analyzing data are data reduction, data presentation and concluding data. The research results show that the preservation efforts carried out by Sanggar Seni Buluh Batuah Sayak Baguno in maintaining Tari Sayak are through protection, development, and utilization The protection of Tari Sayak is carried out through dance training held at Sanggar Seni Buluh Batuah Sayak Baguno in Air Batu Village The development of Tari Sayak carried out by Sanggar Seni Buluh Batuah Sayak Baguno consists of the number of performers or dancers and the development of costumes The number of performers or dancers of Tari Sayak, which initially only consisted of 2 people, has now developed The costume development is now more colorful, previously the skirt only used cloth, now it uses songket and for head coverings, previously using a shawl, now using a kreasi tengkuluk By performing Tari Sayak at certain events, it is already one way to introduce dance to the community.